Marketing Dreams, Manufacturing Heroes: The Transnational Labor Brokering of Filipino Workers - Delias, Dina Marie B. (Kasarinlan: Philippine Journal of Third World Studies; Vol 24 No 1-2 (2009): The Philippines in the WTO, 2011)
“Marketing Dreams and Manufacturing Heroes” is a catchy phrase that captures the reality of many transnational workers and professionals. The idea alludes to how personal aspirations are framed within the market structure. It points out that the image of nobleness of foreign workers (i.e. as bagong bayani or new hero) is a project of the market, the state, and by Filipinos working abroad themselves. Thus said, this book looks into how the market attaches itself to personal values, framing the latter so that people desire being integrated into the global labor force. This process (tenuously) unites personal values (as aspirations and dreams) and market objectives (as profit and productivity). In Guevarra’s book, the reader gets an understanding of the palatability of going overseas for work as it is underpinned by a “moral economy” where migrant workers are made to feel by the Philippine government and society that they are heroes since they contribute to the economic viability of the country and provide for the economic needs of their families.